Correlates of real-world goal-directed behavior in schizophrenia. Issue 6 (12th April 2023) - Merchant, Jaisal T.; Moran, Erin K.; Strube, Michael J.; Barch, Deanna M.
Abstract: Background: Deficits in goal-directed behavior (i.e. behavior conducted to achieve a specific goal or outcome) are core to schizophrenia, difficult to treat, and associated with poor functional outcomes. Factors such as negative symptoms, effort-cost decision-making, cognition, and functional skills have all been associated with goal-directed behavior in schizophrenia as indexed by clinical interviews or laboratory-based tasks. However, little work has examined whether these factors relate to the real-world pursuit of goal-directed activities in this population. Methods: This study aimed to fill this gap by using Ecological Momentary Assessment (four survey prompts per day for 1 week) to test hypotheses about symptom, effort allocation, cognitive, and functional measures associated with planned and completed goal-directed behavior in the daily lives of 63 individuals with schizophrenia. Results: Individuals with schizophrenia completed more goal-directed activities than they planned [ t (62) = −4.01, p < 0.001]. Motivation and pleasure (i.e. experiential) negative symptoms, controlling for depressive symptoms, negatively related to planned goal-directed behavior [odds ratio (OR) 0.92, p = 0.005]. Increased effort expenditure for high probability rewards (planned: OR 1.01, p = 0.034, completed: OR 1.01, p = 0.034) along with performance on a daily functional skills task (planned: OR 1.04, p = 0.002, completed: OR 1.03, p = 0.047) negatively related to both planned and completed goal-directed activity. Conclusions: Our results present correlates of real-world goal-directed behavior that largely align with impaired ability to make future estimations in schizophrenia. This insight could help identify targeted treatments for the elusive motivated behavior deficits in this population.